The National Institutes of Health Stroke Scale is comparable to the ICH score in predicting outcomes in spontaneous acute intracerebral hemorrhage - Kazaryan, Suzie A.; Shkirkova, Kristina; Saver, Jeffrey L.; Liebeskind, David S.; Starkman, Sidney; Bulic, Sebina; Poblete, Roy; Kim-Tenser, May; Guo, Shujing; Conwit, Robin; Villablanca, Pablo; Hamilton, Scott; et al. (Frontiers in Neurology, 2024)
Background Validating the National Institutes of Health NIH Stroke Scale (NIHSS) as a tool to assess deficit severity and prognosis in patients with acute intracerebral hemorrhage would harmonize the assessment of intracerebral hemorrhage (ICH) and acute ischemic stroke (AIS) patients, enable clinical use of a readily implementable and non-imaging dependent prognostic tool, and improve monitoring of ICH care quality in administrative datasets. Methods Among randomized trial ICH patients, the relation between NIHSS scores early after Emergency Department arrival and 3-month outcomes of dependency or death (modified Rankin Scale, mRS 3–6) and case fatality was examined. NIHSS predictive performance was compared to a current standard prognostic scale, the intracerebral hemorrhage score (ICH score). Results Among the 384 patients, the mean age was 65 (±13), with 66% being male. The median NIHSS score was 16 (interquartile range (IQR) 9–25), the mean initial hematoma volume was 29 mL (±38), and the ICH score median was 1 (IQR 0–2). At 3 months, the mRS had a median of 4 (IQR 2–6), with dependency or death occurring in 70% and case fatality in 26%. The NIHSS and ICH scores were strongly correlated (r = 0.73), and each was strongly correlated with the 90-day mRS (NIHSS, r = 0.61; ICH score, r = 0.62). The NIHSS performed comparably to the ICH score in predicting both dependency or death (c = 0.80 vs. 0.80, p = 0.83) and case fatality (c = 0.78 vs. 0.80, p = 0.29). At threshold values, the NIHSS predicted dependency or death with 74.1% accuracy (NIHSS 17.5) and case fatality with 75.0% accuracy (NIHSS 18.5). Conclusion The NIHSS forecasts 3-month functional and case fatality outcomes with accuracy comparable to the ICH Score. Widely documented in routine clinical care and administrative data, the NIHSS can serve as a valuable measure for clinical prognostication, therapy development, and case-mix risk adjustment in ICH patients. Clinical trial registrationClinicaltrials.gov, NCT00059332.